2013
DOI: 10.3109/13816810.2013.768674
|View full text |Cite
|
Sign up to set email alerts
|

TBK1and Flanking Genes in Human Retina

Abstract: Purpose The gene that causes normal tension glaucoma (NTG) in a large pedigree was recently mapped to a region of chromosome 12q14 (GLC1P) that contains the genes TBK1, XPOT, RASSF3, and GNS. We sought to investigate the structure of the chromosome 12q14 duplication and explore the ocular expression of GLC1P locus genes. Methods The location of the chromosome 12q14 duplication in this pedigree was examined with fluorescent in situ hybridization (FISH) using probes for TBK1 and GNS. The expression pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Recently, duplication of TBK1 gene locus has been reported in NTG, although no disease-causing mutations in TBK1 have been reported [ 6 ]. Duplication of TBK1 gene locus in NTG patients was associated with increased transcript levels of TBK1 in retina [ 6 , 68 ]. Gene duplication and increased transcript levels could probably result in increased protein level and activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, duplication of TBK1 gene locus has been reported in NTG, although no disease-causing mutations in TBK1 have been reported [ 6 ]. Duplication of TBK1 gene locus in NTG patients was associated with increased transcript levels of TBK1 in retina [ 6 , 68 ]. Gene duplication and increased transcript levels could probably result in increased protein level and activity.…”
Section: Discussionmentioning
confidence: 99%
“…22 Second, TBK1 is specifically expressed in the ganglion cells and the nerve fiber layer of the human retina, which are involved in the pathogenesis of glaucoma. 15,23 Third, OPTN binds the TBK1 protein, particularly in the presence of the recurrent severe glaucoma-causing mutation E50K in the OPTN gene. 24 Interestingly, 3 known normal-tension glaucoma genes (TBK1, OPTN, and TLR4) each encode proteins that directly interact with each other in a biological pathway that activates autophagy, 25,26 a process by which intracellular materials (eg, proteins, organelles, or pathogens) are degraded.…”
mentioning
confidence: 99%
“…We previously demonstrated that TBK1 is specifically localized to the retinal ganglion cells in the human retina (27,61). In this report, we identify native mouse Tbk1 in the inner and outer nuclear layer cells as well as in the retinal ganglion cells in the retinae of wild-type and Tg-TBK1 mice.…”
Section: Discussionmentioning
confidence: 60%